1999
DOI: 10.1080/016502599383577
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Play Preferences, Construction Play with Blocks, and Visual-spatial Skills: Are they Related?

Abstract: Fifty-one preschoolers' play preferences, skills at assembling block structures, and spatial abilities were recorded in this study. There were no sex differences in children's visual-spatial skills, and play with art materials and children's free and structured play with blocks were related to spatial visualisation. Two patterns emerged from the ndings: (1) activity and Requests for reprints should be sent to Yvonne M. Caldera, Department of Human Development and Family Studies,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
2
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 30 publications
1
95
2
5
Order By: Relevance
“…As Hughes (2012) puts it, during object play "children experience the world by exploring the tactile and cognitive properties of objects" (p. 83). This form of play constitutes 10% to 15% of all behaviors in Western early childhood settings (Smith & Connolly, 1980 as cited in Bjorklund, 2012) and has been shown to be related to higher levels of problem-solving skills (e.g., Sylva, Bruner, & Genova, 1976), creativity (e.g., Johnson, Christie, & Wardle, 2005), and spatial-mathematical reasoning (Caldera et al, 1999). Other scholars have suggested the possible role of object play in helping children discover and explore causal relationships and mechanisms embedded in objects (Bjorklund & Gardiner, 2010).…”
Section: "Play Is the Highest Form Of Research"-albert Einsteinmentioning
confidence: 99%
See 2 more Smart Citations
“…As Hughes (2012) puts it, during object play "children experience the world by exploring the tactile and cognitive properties of objects" (p. 83). This form of play constitutes 10% to 15% of all behaviors in Western early childhood settings (Smith & Connolly, 1980 as cited in Bjorklund, 2012) and has been shown to be related to higher levels of problem-solving skills (e.g., Sylva, Bruner, & Genova, 1976), creativity (e.g., Johnson, Christie, & Wardle, 2005), and spatial-mathematical reasoning (Caldera et al, 1999). Other scholars have suggested the possible role of object play in helping children discover and explore causal relationships and mechanisms embedded in objects (Bjorklund & Gardiner, 2010).…”
Section: "Play Is the Highest Form Of Research"-albert Einsteinmentioning
confidence: 99%
“…Children's play with these simple, three-dimensional geometric building shapes has been linked to the development of convergent and divergent problem-solving skills (Pepler & Ross, 1981), spatial language (Ferrera, Hirsh-Pasek, Newcombe, Golinkoff, & Lam, 2011), logico-mathematical knowledge (Kamii, Miyakawa, & Kato, 2004), and spatial visualization abilities (Caldera et al, 1999) in young children. For example, Caldera et al (1999) conducted in-depth observations of 60 preschool children's structured and unstructured play with blocks and assessed the relationship between particular building behaviors and children's spatial skills. Caldera et al found that complexity of building strategies and interest and involvement in play activity were related to spatial visualization (i.e., ability to make mental manipulations of spatial information) and perceptual field independence (i.e., ability to focus on relevant features of an object outside of context).…”
Section: Object Play and The Exploration Of Physical Science Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies have focused on the relationship between building-block play and mathematics, trying to understanding what mechanisms allow the transformation of LEGO-play skills into calculation skills. In the scientific literature, the relationship between play, mathematics, and visuo-spatial skills has been widely explored (Tracy, 1987;Brosnan, 1998;Caldera et al, 1999;Hegarty & Kozhevnikov 1999;Casey et al, 2008;Casey, Pezaris, & Bassi, 2012;Oostermeijer, 2014;Nath, 2014), emphasising the role that mental imagery may play in this relationship. Mental imagery has been investigated in connection with both mathematics and games, but the mediating role that mental imagery plays between building-block play and mathematics, which may be more relevant, has rarely been considered.…”
mentioning
confidence: 99%
“…While the traditional philosophy of spatial skill gaps has to do with gender differences, recent studies are pointing out that environmental factors are influential as well [17,42,21,43,44,45,46,5]. Factors that have been found positively impacting spatial skills include playing video games, musical experience, art, and childhood construction toys (Legos, Lincoln Logs, etc.…”
Section: Recommendations For Enhancing Spatial Skills (Practitioners)mentioning
confidence: 99%